UPAYA MENINGKATKAN CAPAIAN IKU PERGURUAN TINGGI MELALUI KEGIATAN SK-MBKM MANDIRI - Herianto, Edy; Rispawati, Rispawati; Istiningsih, Siti; Asrin, Asrin (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
IKU is a performance measurement system used to evaluate the performance of higher education institutions in Indonesia. Nine forms of learning activities (BKP) are the primary support for achieving the PT's IKU 2. FKIP is one of the faculties at Mataram University, which has a strategic role in filling IKU 2. To fulfill this expectation, outreach activities and workshops must be carried out. Through outreach activities and workshops by presenting representatives of lecturers and students from all study programs, FKIP hopes that PT IKU's achievements can increase by the targets set by the Ministry of Education, Culture, Research, Technology, and Higher Education. The results of the socialization and workshop activities showed that (1) there was an increase in participants' (lecturers and students') understanding of the importance of MBKM Mandiri, and (2) students formulated various BKP options as a manifestation of their participation in MBKM. Based on these results, the recommendation is that constructive support from each study program is needed to guide and train students to choose the right BKP according to their needs and potential.